2021
DOI: 10.12688/f1000research.74972.1
|View full text |Cite
|
Sign up to set email alerts
|

The association between therapeutic plasma exchange and the risk of mortality among patients critically ill with COVID-19: a meta-analysis

Abstract: Background: Cytokine storm has been widely known to contribute to the development of the critical condition in patients with coronavirus disease 2019 (COVID-19), and studies had been conducted to assess the potential aspect of cytokine storm elimination by performing therapeutic plasma exchange (TPE). However, contradictory findings were observed. The objective of this study was to assess the association between TPE and the reduction of mortality of critically ill COVID-19 patients. Methods: A meta-analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Among the patients, 29 were men, and 31 were women. The mean age of the patients was 67.3 + 12 years (24-90 years), and the mean body mass index (BMI) was 25.5 ± 3 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), consisting of 25.8 ± 2.9 in the male and 25.2 ± 3.1 in the female patients (P = 0.47). The mean hemoglobin level was 12.9 ± 1.6 g/dl in the men and 11.7 ± 1.5 g/dl in the women (P = 0.008).…”
Section: Resultsmentioning
confidence: 99%
“…Among the patients, 29 were men, and 31 were women. The mean age of the patients was 67.3 + 12 years (24-90 years), and the mean body mass index (BMI) was 25.5 ± 3 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), consisting of 25.8 ± 2.9 in the male and 25.2 ± 3.1 in the female patients (P = 0.47). The mean hemoglobin level was 12.9 ± 1.6 g/dl in the men and 11.7 ± 1.5 g/dl in the women (P = 0.008).…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this meta‐analysis was not to investigate the impact of TPE on mortality, ICU stays, and mechanical ventilation only but also to explore the impact of TPE on the key disease pathogenesis mediators such as IL‐6, ferritin, D‐dimer, LDH, and other disease biomarkers. Furthermore, the study includes a larger number of studies and therefore, more patients than the two previously reported systematic reviews 26,27 . A comparison between this study and the two previously published systematic reviews is shown in (Table 4).…”
Section: Discussionmentioning
confidence: 97%
“…However, published studies are conflicting and inconsistent. The published meta‐analyses had different results and had not evaluated all outcomes that should be evaluated, although the small number of studies included 26,27 . Moreover, multiple studies were published and not included in the previous meta‐analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence supports the incremental efficacy of corticosteroids alone or in combination with tocilizumab/JAKi in moderate to severe and critical COVID-19 [ 4 , 35 , 36 ]. Therapeutic plasma exchange also appears to have potential benefits in reducing the risk of mortality among critically ill COVID-19 patients [ 37 ]. Of this therapeutic arsenal, tocilizumab is the most studied drug in the setting of severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%